1995
DOI: 10.1063/1.115091
|View full text |Cite
|
Sign up to set email alerts
|

Compensating acceptors and donors in nitrogen δ-doped ZnSe layers studied by photoluminescence and photoluminescence excitation spectroscopy

Abstract: The compensating acceptors and donors in nitrogen δ-doped ZnSe epilayers grown by molecular beam epitaxy using a nitrogen rf-plasma source are studied by means of photoluminescence (PL) and photoluminescence excitation spectroscopy (PLE). The temperature dependence of PL and PLE spectra obtained from the nitrogen δ-doped layers is investigated in detail, and a deep acceptor and a deep donor with ionization energies of ∼170 and ∼88 meV are reported for the nitrogen δ-doped layers. These two deep centers are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It has been shown that ␦-doping can suppress the complex-type defects in various materials such as in GaAs and ZnSe for either type of doping. [20][21][22] Thus, with the ͑NϩTe͒␦-doping in Zn 1Ϫy Cd y Se and Zn 1Ϫx Mg x Se ternaries, it is reasonable to expect that the complex-type compensation defects should be reduced. Furthermore, the impurity-host bond ͑Mg-N and Cd-N bonds͒ breaking ͑DX-like center defects͒ should be reduced by depositing nitrogen on the Zn-terminated surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ␦-doping can suppress the complex-type defects in various materials such as in GaAs and ZnSe for either type of doping. [20][21][22] Thus, with the ͑NϩTe͒␦-doping in Zn 1Ϫy Cd y Se and Zn 1Ϫx Mg x Se ternaries, it is reasonable to expect that the complex-type compensation defects should be reduced. Furthermore, the impurity-host bond ͑Mg-N and Cd-N bonds͒ breaking ͑DX-like center defects͒ should be reduced by depositing nitrogen on the Zn-terminated surface.…”
Section: Resultsmentioning
confidence: 99%
“…Proposed compensation defects with nitrogen doping include: ͑1͒ native defects ͑such as vacancies and interstitials͒, ͑2͒ complex defects consisting of nitrogen combined with a native defect ͑such as N Se -V Se and N Se -Zn i ), ͑3͒ nitride complex defects ͑such as Se 4 N 4 and Cd 3 N 2 ͒, ͑4͒ associated nitrogen compensation centers ͓such as Zn-͑N Se ) n , and N Se -N Zn ͔, and ͑5͒ bond breaking defects ͑DX-like centers, such as impurityhost and host-host bond breaking͒. [7][8][9] In fact, many theoretical and experimental studies in the past years have been devoted to examining which defects dominate the compensation phenomena in ZnSe:N. [10][11][12][13][14] These investigations have led to the conclusion that only some of the proposed compensation defects, such as the N Se -V Se complexes, the nitride complexes and the host-host bond breaking defects, may have a significant effect in ZnSe:N.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is the reason for previous discrepancies. In 1995, a deep acceptor and a deep donor with ionization energies of ϳ170 and ϳ88 meV in heavily N-doped ZnSe were detected by using photoluminescence and photolumine excitation spectroscopy, 14 and it was proposed that they were N clusters, i.e., N Se -Zn-N Se for the deep acceptor and N Se -N Zn for the deep donor, as shown in Fig. 1͑b͒.…”
Section: Resultsmentioning
confidence: 99%
“…Delta doping has been proposed to reduce complex-type defects. [8][9][10] For ZnSe:N, Zhu et al have proposed that the N Se -V Se complex can be suppressed by ␦ doping. 8 Ϫ3 .…”
mentioning
confidence: 99%